Immunogenicity and efficacy following sequential parenterally-administered doses of Salmonella Enteritidis COPS:FliC glycoconjugates in infant and adult mice. - Scott M Baliban; Brittany Curtis; Deanna Toema; Sharon M Tennant; Myron M Levine; Marcela F Pasetti; Raphael Simon (PLoS Neglected Tropical Diseases)
In sub-Saharan Africa, invasive nontyphoidal Salmonella (iNTS) infections with serovars S. Enteritidis, S. Typhimurium and I 4,[5],12:i:- are widespread in children < 5 years old. Development of an efficacious vaccine would provide an important public health tool to prevent iNTS disease in this population. Glycoconjugates of S. Enteritidis core and O-polysaccharide (COPS) coupled to the homologous serovar phase 1 flagellin protein (FliC) were previously shown to be immunogenic and protected adult mice against death following challenge with a virulent Malian S. Enteritidis blood isolate. This study extends these observations to immunization of mice in early life and also assesses protection with partial and full regimens. Anti-COPS and anti-FliC serum IgG titers were assessed in infant and adult mice after immunization with 1, 2 or 3 doses of S. Enteritidis COPS:FliC alone or co-formulated with aluminum hydroxide or monophosphoryl lipid A (MPL) adjuvants. S. Enteritidis COPS:FliC was immunogenic in both age groups, although the immune responses were quantitatively lower in infants. Kinetics of antibody production were similar for the native and adjuvanted formulations after three doses; conjugates formulated with MPL elicited significantly increased anti-COPS IgG titers in adult but not infant mice. Nevertheless, robust protection against S. Enteritidis challenge was seen for all three formulations when three doses were given either during infancy or as adults. We further found that significant protection could be achieved with two COPS:FliC doses, despite elicitation of modest serum anti-COPS IgG antibody titers. These findings guide potential immunization strategies that may be translated to develop a human pediatric iNTS vaccine for sub-Saharan Africa.